The Effect of Cognitive Behavioral Therapy on Anxiety and Depression Among Students in Science Education: A Meta-Analysis - Nur Hasan; Khoirunnisa, Riza Noviana; Nurtamam, Mohammad Edy; Fauzi, Rizal Ula Ananta; Santosa, Tomi Apra; Nugraha, Aat Ruchiat; Sjoraida, Diah Fatma; Sarnoto, Ahmad Zain (Science Education and Application Journal, 2025)
The Effect of Cognitive Behavioral Therapy on Anxiety and Depression Among Students in Science Education: A Meta-Analysis. This meta-analysis aims to evaluate the impact of Cognitive Behavioral Therapy (CBT) on anxiety and depression specifically within the context of science learning. This study was conducted by integrating and evaluating the results of previous relevant studies to provide a comprehensive understanding of the effectiveness of CBT in dealing with mental health problems in the adolescent population. The study sample consisted of 16 studies published between 2010 and 2023, which met inclusion criteria, such as experimental or quasi-experimental design, use of standardized scales to measure anxiety and depression, and a focus on CBT interventions. The meta-analysis revealed a significant positive effect of CBT on reducing anxiety and depression in science learning contexts (d = 0.945; z = 7.052; p < 0.001)."These findings support the use of CBT as a key approach in mental health interventions for adolescents, particularly in the context of education and primary health services.